Physiological profile of Swiss elite alpine skiers - a 10-year longitudinal comparison - Maffiuletti, N. A.; Jordan, K.; Spring, H.; Impellizzeri, F. M.; Bizzini, M. (Science and Skiing IV, 2009)
INTRODUCTION: Alpine skiing requires muscular strength, aerobic and anaerobic power, and a variety of complex motor abilities. The objective of this study was to describe the physiologtcal profile of a large number of elite male alpine skiers over 10 consecutive years.